IMPLEMENTASI NILAI KARAKTER DISIPLIN MELALUI METODE BERNYANYI UNTUK ANAK USIA DINI DI PAUD MIFTAHUL HUDA NEGERI AGUNG - Yawati, Ani; Ariyanti, Leni (Institut Agama Islam Ngawi, 2023)
Character education is an activity that is carried out consciously and planned in facilitating and helping students to know good and noble things, love them, have strong competence to fight for goodness and nobility and be able to make wise decisions. The singing method is a lesson that is submitted by the teacher singing/singing in a melodious voice and pleasant tones as an effort to convey various information and knowledge. Discipline is a moral attitude of students that is formed through the process of a series of behaviors that show the values ​​of obedience, order, and delay based on moral references. This type of research is qualitative, while the purpose of this research is to find out the Implementation of Discipline Character Values ​​Through the Singing Method for Early Childhood at Early Childhood Education Miftahul Huda Negeri Agung Academic Year 2022/2023. The data obtained through several methods, namely interviews, observation and documentation. Based on the results of analysis of interview data, observation and documentation obtained, it can be concluded that the Implementation of Discipline Character Values ​​Through the Singing Method for Early Childhood at Miftahul Huda Negeri Agung Academic Year 2022/2023 increases student discipline, namely Come to school on time, pay attention to the teacher during KBM, complete assignments according to the time, leave the class according to the specified time, dispose of trash in its place.